2001
DOI: 10.1046/j.0014-2956.2001.02589.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the SERCA Ca2+ pumps by curcumin

Abstract: Curcumin is a compound derived from the spice, tumeric. It is a potent inhibitor of the SERCA Ca 2þ pumps (all isoforms), inhibiting Ca 2þ -dependent ATPase activity with IC 50 values of between 7 and 15 mM. It also inhibits ATPdependent Ca 2þ -uptake in a variety of microsomal membranes, although for cerebellar and platelet microsomes, a stimulation in Ca 2þ uptake is observed at low curcumin concentrations (,10 mM). For the skeletal muscle isoform of the Ca 2þ pump (SERCA1), the inhibition of curcumin is non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(65 citation statements)
references
References 44 publications
(64 reference statements)
8
53
0
2
Order By: Relevance
“…Study has shown that the activity of SERCA can be inhibited by curcumin with IC 50 values of between 7 and 15 mM. 22) These inhibition doses of curcumin are similar to the LD 50 values against zebrafish embryos and larvae. Moreover, knockdown SERCA2 expression by morpholino injection in zebrafish fertilized eggs results in defective cardiac development, as well as slower heartbeat and weak heart contractility.…”
Section: Dosage-dependent Toxic Effects Of Curcumin Exposurementioning
confidence: 63%
“…Study has shown that the activity of SERCA can be inhibited by curcumin with IC 50 values of between 7 and 15 mM. 22) These inhibition doses of curcumin are similar to the LD 50 values against zebrafish embryos and larvae. Moreover, knockdown SERCA2 expression by morpholino injection in zebrafish fertilized eggs results in defective cardiac development, as well as slower heartbeat and weak heart contractility.…”
Section: Dosage-dependent Toxic Effects Of Curcumin Exposurementioning
confidence: 63%
“…Therefore, we conclude that curcumin induced formation of ROS causes an increase in cytosolic Ca 2+ due to opening of non-selective and L-type voltage-gated calcium channels and release of Ca 2+ from intracellular stores. Inhibition of SR Ca 2+ -ATPase by curcumin has already been established previously [49]. The increase in cytosolic Ca 2+ causes cellular damage and death through disruption of the cytoskeletal networks and the action of Ca 2+ stimulated catabolic enzymes, such as protease, phospholipases, and endonucleases.…”
Section: Discussionmentioning
confidence: 97%
“…Following addition of myosin, ATP hydrolysis was calculated from the P i released during a 15-min incubation at 30°C. The P i assay was adapted to 96-well plate format from Bilmen et al (39): the 50-l ATPase reactions were stopped by the addition of 150 l of chilled 0.2 M sodium acetate (pH 4.0), 0.25% (w/v) copper sulfate. This was followed by 25 l of 5% (w/v) ammonium molybdate and 25 l of 5% (w/v) sodium sulfite, 2% (w/v) p-methylaminophenol sulfate.…”
Section: Methodsmentioning
confidence: 99%